2003
DOI: 10.1121/1.1534607
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic wave propagation in double porosity media

Abstract: A study of the propagation of waves in porous media with an interconnected network of pores and micropores of very different characteristic sizes, saturated by a compressible Newtonian fluid, is proposed. With this aim, the homogenization technique for periodic separated scales media, is applied to realistic double porosity materials with motionless skeleton. From preliminary explicit estimations of wavelengths in the two fluid networks, it is shown that the macroscopic descriptions depend on the contrast of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
232
2
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(240 citation statements)
references
References 12 publications
4
232
2
2
Order By: Relevance
“…Indeed, to meet double porosity model requirements, the microporous medium must be sufficiently permeable to acoustical waves, and the micropore characteristic size must be greater than 10 lm. 24 As the fiber inner diameter is close to that limit with a value of about 22 lm, the acoustical wave should not penetrate much into the fibers' internal porosity. We also used the limp model in which the effective density of the rigid-frame equivalent fluid medium is corrected as per Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, to meet double porosity model requirements, the microporous medium must be sufficiently permeable to acoustical waves, and the micropore characteristic size must be greater than 10 lm. 24 As the fiber inner diameter is close to that limit with a value of about 22 lm, the acoustical wave should not penetrate much into the fibers' internal porosity. We also used the limp model in which the effective density of the rigid-frame equivalent fluid medium is corrected as per Eq.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that sound absorption at the lower end of the frequency range of interest (∼ 1-3 kHz) can be improved by using 'double-porosity' [9,10] multilayered [11][12][13] or stratified [14,15] porous structures. To date, however, very few studies have been carried out on the acoustic properties of porous materials at high temperatures [16] and/or in a rapid gas flow environment, such as that in the exhaust of a gas turbine aeroengine.…”
mentioning
confidence: 99%
“…However, it is not very common knowledge that general duty motors are available (at little or no cost premium) that are up to 10 dB(A) or more quieter than typical units as direct replacements. The best approach is to feed these motors into the system over a period of time so that all replacement motors are quiet motors [3], [4] and [14]- [16].…”
Section: E Electric Motorsmentioning
confidence: 99%
“…The noise produced by automobiles may depends of the engine size and type of the vehicle , see Table I. [3], and [4] International Journal of Modeling and Optimization, Vol. 3, No.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation